In search of an effective and proportionate strengthening of the constitutional right to health protection - Gómez Franco, Tomás; Repullo Labrador, José Ramón (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2015)
The right to health protection in the Spanish Constitution loses effectiveness in a context of increasing needs, expenditure growth and implementation of cost containment policies. Looking ahead to the coming debates, it is essential to analyze the principles that would allow order, rank and link health needs and Constitutional protection. On this basis, a proposal is made to enrich the political, legal and social debate, involving the articulation of the three types of Constitutional protection -reinforced, tutored, and selective, with twelve categories of need in the three dimensions of individual, social and economic harm.
Keywords: right to health; Spanish Constitution; health needs; healthcare protection; healthcare coverage